DISTRIBUSI ZAKAT FITRAH DI KELURAHAN BENTENG KEC. BARANTI KABUPATEN SIDRAP (Tinjauan Hukum Islam) - Basri, Rusdaya; Wahid, Amelia (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
This study is a survey research conducted in urban Fort Subdistrict Baranti Sidrap. This study aims to determine how the distribution of tithes in the Village of Fort Subdistrict Baranti Sidrap and how the distribution of tithes in the Village of Fort Subdistrict Baranti Sidrap and review its Islamic law. This research is qualitative with a phenomenological approach to data collection and juridical using interview techniques, observation, documentation and library research. The data analysis technique that is both inductive and deductive. The results of this study indicate that 1) Distribution of tithes in the Village of Fort Subdistrict Baranti Sidrap still follow traditional customs of local communities by distributing zakat fitrah directly to the beneficiary as poor neighbor , imam of the mosque, an employee of Personality, tutor children and shamans , 2) the distribution of tithes directly Fortress Village society is legitimate in terms of Islamic law , but distribution through zakat management institutions will be much more effective .